2017
DOI: 10.1089/zeb.2016.1405
|View full text |Cite
|
Sign up to set email alerts
|

Highest Diploid Number Among Gymnotiformes: First Cytogenetic Insights into Rhabdolichops (Sternopygidae)

Abstract: We report the first comparative cytogenetic analysis of two species from electrogenic fish of genus Rhabdolichops (Sternopygidae, Gymnotiformes): Rhabdolichops troscheli and Rhabdolichops cf eastwardi. R. troscheli has 2n = 54 (fundamental number [FN] = 66), whereas R. cf. eastwardi has 2n = 74 (FN = 78). C-banding revealed centromeric constitutive heterochromatin in both species. Ag-NORs mapped on pair 6 in R. troscheli and pair 30 in R. cf eastwardi. Fluorescense in situ hybridization with 18S rDNA probes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…D. cuneata represents an exception, given the increase in karyotype by two chromosomes with respect to the predicted ancestral karyotype of Pleuronectiformes. Chromosome fission is a plausible way for this diploid number to have been reached in D. cuneata , as has already been proposed for fish species of the genus Rhabdolichops of the Gymnotiformes order [ 42 ].…”
Section: Discussionmentioning
confidence: 91%
“…D. cuneata represents an exception, given the increase in karyotype by two chromosomes with respect to the predicted ancestral karyotype of Pleuronectiformes. Chromosome fission is a plausible way for this diploid number to have been reached in D. cuneata , as has already been proposed for fish species of the genus Rhabdolichops of the Gymnotiformes order [ 42 ].…”
Section: Discussionmentioning
confidence: 91%
“…FISH probes for 18S and 5S rDNA were amplified by polymerase chain reaction (PCR) using genomic DNA from C. johanna , and the following primer pairs: 18S rDNA (18SF-5′ CCG CTT TGG TGA CTC TTG AT and 18SR-5′ CCG AGG ACC TCA CTA AAC CA) of Gross et al (2010); and 5S rDNA (5SF-5′ GCC ACA CCA CCC CTG AAC AC and 5SR-5′ GCC TAC GAC ACC TGG TAT TC) of Suarez et al (2017). In each PCR reaction were used: 100 ng/μl genomic DNA, 2,5 μl of 10× reaction buffer, 0.75 MgCl, 2,0 μl of DNTP mix (2 mM), 1 μl of each primer (10 mM), 1U of enzyme Taq Polymerase (Invitrogen) and 16.5 μl of pure water.…”
Section: Methodsmentioning
confidence: 99%
“…Cytogenetics has been an important tool in cytotaxonomy and has proved to be very useful in understanding the evolutionary processes behind the diversification of Gymnotus . The Gymnotiformes order has considerable variation, not only in diploid number (from 2 n = 24 in Apteronotus albifrons , Howell, 1972 ; Almeida-Toledo et al, 1981 ; Mendes et al, 2012 ; to 2 n = 74 in Rhabdolichops cf eastward , Suárez et al, 2017 ) but also in the karyotype formula and location of repetitive sequences (Fernandes et al, 2005 ; Almeida-Toledo et al, 2007 ; Silva et al, 2009 ; da Silva et al, 2013 ; Jesus et al, 2016 ; Araya-Jaime et al, 2017 ; Batista et al, 2017 ; Sousa et al, 2017 ; Takagui et al, 2017 ). Recently, fluorescence in situ hybridization (FISH), has played an important role in understanding the genome structure of fish species (Yi et al, 2003 ; Cabral-de-Mello and Martins, 2010 ; Martins et al, 2011 ; Vicari et al, 2011 ; Gornung, 2013 ; Knytl et al, 2013 ; Yano et al, 2017 ) and molecular cytogenetic studies in Gymnotiformes have shown dynamic reorganization, including pericentric inversions observed through repetitive DNA position (Fernandes et al, 2017 ), sequence dispersion via transposable elements and the association between different repetitive sequences (Utsunomia et al, 2014 ; da Silva et al, 2016 ; Machado et al, 2017 ) and the presence of different sex chromosome systems (Margarido et al, 2007 ; Henning et al, 2008 , 2011 ; da Silva et al, 2011 , 2014 ; Almeida et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%